2015
DOI: 10.3354/meps11170
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory and the resilience of Caribbean coral reefs: knowledge gaps and implications for management

Abstract: Resale or republication not permitted without written consent of the publisherBlue parrotfish Scarus coeruleus cropping algae on a reef.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(150 citation statements)
references
References 208 publications
3
141
1
5
Order By: Relevance
“…This may be especially true in degraded, overfished, and heavily impacted ecosystems, as in our Caribbean study area. In the Indo-Pacific, the relatively rapid recovery of reefs following disturbance has been attributed to robust herbivore communities519, but our results are the first, to our knowledge, to suggest a similar potential due to functional redundancy in the herbivore community of the Caribbean. As aspects of our study system vary relative to some other well-studied areas of the Caribbean, which experience higher wave exposure and water flow, it will be important to monitor impacts of small bodied herbivores to determine the ecological contexts where similar dynamics can and do occur.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This may be especially true in degraded, overfished, and heavily impacted ecosystems, as in our Caribbean study area. In the Indo-Pacific, the relatively rapid recovery of reefs following disturbance has been attributed to robust herbivore communities519, but our results are the first, to our knowledge, to suggest a similar potential due to functional redundancy in the herbivore community of the Caribbean. As aspects of our study system vary relative to some other well-studied areas of the Caribbean, which experience higher wave exposure and water flow, it will be important to monitor impacts of small bodied herbivores to determine the ecological contexts where similar dynamics can and do occur.…”
Section: Discussionmentioning
confidence: 55%
“…However, recent evidence suggests that coral-algal phase shifts may be less consistent than previously assumed16. Uncertainty in the frequency and occurrence of phase shifts questions our mechanistic understanding of coral reef dynamics and our ability to predict coral resilience and recovery11171819.…”
mentioning
confidence: 97%
“…We find that biodiversity is equally and often more important than water quality, nutrient supply, and human influence in controlling the global distribution of reef fish biomass, and that more diverse fish communities are more resilient to impacts of changing climate. Moreover, both species richness and functional trait diversity contributed roughly equally to fish biomass globally, generalizing local inferences that reef fish trophic interactions (45,46) and functional diversity (47)(48)(49) are key mediators of the community structure and resilience of coral reef ecosystems. Because reef fish biomass provides an important protein source for many people, particularly in the developing world, our results suggest that management to sustain reef fish diversity, of both species and functional types, will also promote higher productivity of fish biomass and higher resilience of that ecosystem service in the face of rising and more variable temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The first has been to correlate macroalgal cover with herbivore biomass among reefs that vary in herbivore biomass, either naturally or as a result of differences in fishing pressure, and the second has been to observe responses of reefs following fishing bans43. While useful in exposing broad patterns, these approaches can be difficult to interpret due to the many other factors that can affect establishment and growth of algae (e.g., nutrient loading, light, sedimentation, type of herbivores present)44. Despite this, non-experimental studies have suggested that the relationship between herbivory and macroalgal cover can be non-linear15.…”
Section: Discussionmentioning
confidence: 99%